1995
DOI: 10.1136/jmg.32.5.399
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of the CCG polymorphic region adjacent to the CAG triplet repeat of the HD gene in normal and HD chromosomes.

Abstract: The CAG expansion responsible for Huntington's disease (HD) is followed by an adjacent polymorphic CCG repeat region which may interfere with a PCR based diagnosis. We have sequenced this region in 52 unrelated HD patients, from both normal and HD chromosomes. Fifty percent of the normal alleles were (CCG)7(CCT)2, 48% (CCG)IO(CCT)2, and 2% (CCG)7(CCT)3. In contrast (CCG)7(CCT)2 was found in 85% ofthe HD alleles which represents significant linkage disequilibrium with the HD mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 4 publications
0
21
0
3
Order By: Relevance
“…c The alleles of the VNTR loci in the HD promoter are named according to the number of repeat units. d The variation in the length of the polyproline repeat stems from variation in the number of CCGs and/or CCTs (39). Sequencing of patients from families with known haplotypes showed that the allele designated ÔCCG7' was (CCG) 7 (CCT) 2 , whereas the allele designated ÔCCG8' was (CCG) 7 (CCT) 3 .…”
Section: Resultsmentioning
confidence: 99%
“…c The alleles of the VNTR loci in the HD promoter are named according to the number of repeat units. d The variation in the length of the polyproline repeat stems from variation in the number of CCGs and/or CCTs (39). Sequencing of patients from families with known haplotypes showed that the allele designated ÔCCG7' was (CCG) 7 (CCT) 2 , whereas the allele designated ÔCCG8' was (CCG) 7 (CCT) 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Another explanation for the difference in prevalence of HD between Asian and non‐Asian populations may be related to the CCG polymorphic region adjacent to the CAG triplet repeat of the HD gene. In Caucasian populations, expanded CAG repeat alleles are strongly associated with CCG 7 alleles 30, 33. CCG 7 alleles are present in 67.8% of wild‐type (WT) HTT genes and 94.4% of mutant‐type (MT) HTT genes 30.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data suggests that the prevalence of HD may be over 10 per 100,000 in the UK [ 14 ]. These racial differences in prevalence are accounted for by the differences in CAG tract size, HTT haplotype and CCG polymorphism [ 15 17 ]. The mean CAG repeat length of the normal allele was reported to be significantly longer in the European (18.4 ± 3.7) population compared with the Chinese, Japanese, and Thai (16.4 ± 1.5, 16.6 ± 1.5, and 16.5 ± 1.9, respectively) population [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…HTT haplogroups are known to show a regional difference, and the higher risk haplotype was infrequent in China, Japan, and Thailand [ 18 , 21 , 22 ]. The CCG polymorphic region is located adjacent to the CAG triplet repeat of the HD gene, and there is a linkage disequilibrium between CCG polymorphism and the pathological CAG expansion according to the race [ 17 , 23 ]. HTT haplogroup and CCG polymorphism have not yet been studied in Korean HD patients.…”
Section: Discussionmentioning
confidence: 99%